Community structure of seagrass beds in Arakan, South Minahasa Regency - Merly, Sendy L; Wagey, Billy T; Gerung, Grevo S (Universitas Sam Ratulangi, 2013)
Arakan waters is located in front of Arakan Wawontulap district as part of Bunaken National Park. This area has a vast seagrass meadow of 1943.45 ha. Seagrass-Watch method combined with line transect and quadrat methods were used to collected data. Four seagrass species were identified such as Halophila ovalis, Thalassia hemprichii, Enhalus acoroides and Syringodium isoetifolium. Diversity Index (H') was quite high at 1.2071 and was inversely correlated to the value of dominance (D) at 0.3366, and this was supported by the presence of a uniform species (J') of 0.8707. Important Index Value (INP) was highest at station I comprising E. acoroides species, and station II comprising E. acoroides and T. hemprichii, while the third station comprised T. hemprichii. Spatial distribution of the three stations ranged from random to contagious (aggregated)© Perairan Desa Arakan termasuk dalam kawasan Taman Nasional Bunaken wilayah Arakan Wawontulap yang memiliki luas area padang lamun sekitar 1.943,45 Ha. Data dikoleksi menggunakan metode seagrass-watch yang dikombinasikan dengan metoda transek garis dan kuadran. Empat spesies lamun berhasil diidentifikasi yaitu Halophila ovalis, Thalassia hemprichii, Enhalus acoroides dan Syringodium isoetifolium. Nilai Indeks Keanekaragaman (H’) cukup tinggi yakni 1,2071 berbanding terbalik dengan Nilai Dominansi (D) yang rendah yakni 0,3366 dan ditunjang dengan keberadaan spesies yang merata (J’) senilai 0,8707. Indeks Nilai Penting (INP) tertinggi pada Stasiun I diperlihatkan oleh E.acoroides, Stasiun II oleh E.acoroides dan T.hemprichii, dan sedangkan Stasiun III oleh T. hemprichii. Adapun pola penyebaran pada ketiga stasiun ini berkisar antara acak (random) dan mengelompok (contagious)©